Investigation of metallation/transmetallation reactions to synthesize a series of CCC–NHC Co pincer complexes and their X-ray structures. (1st September 2018) - Denny, Jason A.; Lamb, Robert W.; Reilly, Sean W.; Donnadieu, Bruno; Webster, Charles Edwin; Hollis, T. Keith
Graphical abstract: CCC–NHC pincer cobalt complexes were synthesized by transmetallation with an isolated CCC–Zr complex using CoCl2 or Co(acac)3 to yield monomeric, dimeric, and bis-ligated cobalt pincer complexes. Abstract: Formation of Co(III) complexes was achieved via transmetallation with CoCl2 or Co(acac)3 of an isolated CCC–NHC pincer Zr complex. Four new crystal structures are reported, which expand upon the limited scope of first-row transition metal CCC–NHC pincer complexes. DFT computations were utilized to analyze the thermodynamics of cleaving a dimeric cobalt pincer complex with dimethylamine.